1963
DOI: 10.1002/macp.1963.020590102
|View full text |Cite
|
Sign up to set email alerts
|

Streulicht‐ und Viskositätsmessungen an wäßrigen Amyloselösungen. II.

Abstract: ZUSAMMENFASSUNG:An einer Reihe von synthetischen Amylosen in Wasser wurden Streulicht-und Viskositatsmessungen durchgefiihrt. Die Abhhgigkeiten des Triigheitsradius und der Viskositiitszahl [q] vom Polymerisationsgrad zeichnen sich durch keine Besonderheiten aus und entsprechen denen eines verknauelten linearen Fadenmolekiils. Dagegen ergibt sich fiir den 2. Virialkoeffkienten A, eine ungewohnliche Molekulargewichtsabhiingigkeit. Nach vergleichenden Messungen einer Amylose in verschiedenen Losungsmitteln erhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
1

Year Published

1963
1963
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 20 publications
1
23
1
Order By: Relevance
“…However, the chain conformation in this organic solvent has long been controversial as to whether it is a random coil or a semiflexible helix. 6 Conformational energy calculations 2 • 7 -9 predict that amylose should be flexible but locally helical.Very recently, Nakanishi et al 10 demonstrated from light scattering, sedimentation equilibrium, and viscosity measurements on narrow-distribution samples of synthetic amylose at 25°C that the chain conformation in DMSO is a random coil expanded by excluded-volume effect if Mis higher than 10 5 • They, analyzing intrinsic viscosity ([17]) data for M between 342 (the dimer) and 10 4 in terms of the unperturbed helical wormlike (HW) chain, 11 • 12 derived the following conclusions from the estimated HW model parameters: (1) The value of C 00 in DMSO (at 25°C) is about 5, so that without excluded-volume effect, the global conformations in DMSO and aqueous solvents are similar, and (2) though flexible, the amylose chain in DMSO has some helical nature locally. This molecular picture, i.e., an irregular helical conformation with high flexibility, appears to resemble that predicted from conformational calculations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the chain conformation in this organic solvent has long been controversial as to whether it is a random coil or a semiflexible helix. 6 Conformational energy calculations 2 • 7 -9 predict that amylose should be flexible but locally helical.Very recently, Nakanishi et al 10 demonstrated from light scattering, sedimentation equilibrium, and viscosity measurements on narrow-distribution samples of synthetic amylose at 25°C that the chain conformation in DMSO is a random coil expanded by excluded-volume effect if Mis higher than 10 5 • They, analyzing intrinsic viscosity ([17]) data for M between 342 (the dimer) and 10 4 in terms of the unperturbed helical wormlike (HW) chain, 11 • 12 derived the following conclusions from the estimated HW model parameters: (1) The value of C 00 in DMSO (at 25°C) is about 5, so that without excluded-volume effect, the global conformations in DMSO and aqueous solvents are similar, and (2) though flexible, the amylose chain in DMSO has some helical nature locally. This molecular picture, i.e., an irregular helical conformation with high flexibility, appears to resemble that predicted from conformational calculations.…”
mentioning
confidence: 99%
“…M between 342 (the dimer) and 10 4 in terms of the unperturbed helical wormlike (HW) chain, 11 • 12 derived the following conclusions from the estimated HW model parameters: (1) The value of C 00 in DMSO (at 25°C) is about 5, so that without excluded-volume effect, the global conformations in DMSO and aqueous solvents are similar, and (2) though flexible, the amylose chain in DMSO has some helical nature locally. This molecular picture, i.e., an irregular helical conformation with high flexibility, appears to resemble that predicted from conformational calculations.…”
mentioning
confidence: 99%
“…They show analogously high diffusion and low sedimentation exponents in the respective equations [30,41], Table 2 gives the Mark-Houwink constants collected from the published literature.…”
Section: Bergermentioning
confidence: 96%
“…High Mark-Houwink and low sedimentation exponents led Burchard [30] to the conclusion that polybutyl isocyanate (PBIC) molecules behave as stiff highly expanded chains. An early light-scattering study [31] confirmed directly that polyhexyl isocyanate (PHIC) molecules exhibit extraordinarily high radii of gyration.…”
Section: Conformational Behavior In Solutionmentioning
confidence: 99%
“…The depend.ence of intrinsic viscosity on molecular weight to the oligomer level has been investigated for a number of synthetic polymers [5] and for amylose [ 6 ] . Cellulose of low molecular weight obtained by acid hydrolysis was investigated by Vink [7] who showed that the exponent in the modified Staudinger relation, [q] = K Ma approaches zero at the oligomer level but increases to exceed unity at intermediate levels below a degree of polymerization of 100.…”
Section: Introductionmentioning
confidence: 99%